Physicochemical Transformation Of Heavy Metals In Sludge-biochar Produced By Pyrolysis Treatment - Chanaka Udayanga, Withanage Don (2017)
Biochars (BCs) were produced by pyrolysis of dry sewage sludge (DSS) in order to stabilize the heavy metals (HMs). The physicochemical transformations of HMs were studied during pyrolysis at different temperatures (500-700 oC) in a fixed bed reactor. The produced BCs and DSS were introduced into combustion process at 950 oC. The HMs (Cu, Cr, Zn, Ni, As and Mn) were monitored to determine the influence of pyrolysis in terms of enrichment and leachability. Volatilisation tendencies of HMs (except for As) in pyrolysis process were minimal, while the leaching properties of the BCs were lower compared to DSS (except for Zn). After combustion of BCs and DSS, the produced ashes presented comparable HMs leaching and retention characteristics, except for As that had higher retention in the final ash coming from the direct combustion of DSS.